Rheological study of semiconsistant excipients applied in pharmaceutical pomade technology: I. Normalization of the penetrometric measurements - Cereza, A.; Suñé, J. Mª. (Ars Pharmaceutica (Internet), 1969)
Verified the study of statistical significance to reach the possibility of normalization of the penettrometric measurements in terms of the number of experiences, the average of 5 experiences is established as sufficient with an average error of + -5% as a maximum. The circumstances or influencing factors in the method are also studied, verifying how certain factors such as the filling procedure of the container, the number of tests per container, the temperature of the test and the heating temperature are perfectly indictable, with the opposite occurring with the operator factors. and storage time that do not appear to affect the rheological qualities of the excipients under the test conditions.